Non-Abelian Chern-Simons vortices - Lozano, G.S. (2007)
We consider the bosonic sector of an N = 2 supersymmetric Chern-Simons-Higgs theory in 2 + 1 dimensions. The gauge group is U (1) × SU (N) and has Nf flavors of fundamental matter fields. The model supports non-Abelian (axially symmetric) vortices when Nf ≥ N, which have internal (orientational) moduli. When Nf > N, the solutions acquire additional collective coordinates parameterizing their transverse size. We solve the BPS equations numerically and obtain local (Nf = N) and semi-local (Nf > N) string solutions. © 2007 Elsevier B.V. All rights reserved.